Perhitungan Beban Kerja Dan Kebutuhan Sumber Daya Manusia (SDM) Dengan Metode ABK Kes Di Unit Rekam Medis Puskesmas Guntung Payung Banjarbaru - Nirma Yunita; Ermas Estiyana (HB PRESS, 2022)
Workload is the number of types of work that must be completed by professional health workers in 1 (one) year in one health service facility. Planning for Human Resources (HR) needs can be done by calculating using the ABK Kes method. The medical record unit at the Guntung Payung Health Center Banjarbaru has 6 officers, consisting of 3 counter 1 officer and 3 counter 2 officers. All medical record unit officers often have other jobs. This causes the workload of the officers to be more. This study aimed to determine the workload and needs of Human Resources (HR) in the medical record unit at the Guntung Payung Health Center Banjarbaru. This research used a descriptive method. The results and conclusions of this study were the workload in the medical record unit at the Guntung Payung Health Center Banjarbaru using the Full Time Equivalent (FTE) method was overloaded, meaning the workload was high. The need for Human Resources (HR) in the medical record unit of the Guntung Payung Health Center Banjarbaru using the ABK Kes method was 7 people, meaning that the Human Resources (HR) was still lacking, especially at counter 2 requiring the addition of 1 officer.